Scholarship of Teaching and Learning (SoTL) as a complementary outcomes assessment strategy: Case study on unit conversions, including test creation - Morales, Juan C.; González-Espada, Wilson J.; Espinoza, Albert A.; Malave, Amaury J .; Montejo-Valencia, Brian D.; Castillo, Eduardo E.; Traverso Avilés, Luis Miguel (LACCEI, 2024)
The Scholarship of Teaching and Learning (SoTL) involves faculty undertaking systematic and scholarly inquiry about student learning, using the findings to improve their own students’ achievement, and sharing the results with the broader higher education community. This paper proposes that SoTL may be used as a complementary and deeper outcomes assessment strategy compared to the typical strategy of using student coursework (exams, projects, lab reports, etc.) to conduct direct assessment based on a rubric. The case study of this SoTL intervention was conversion of units of measure. The motivation for the inquiry was based on the faculty’s consensus that many students lack proficiency with this fundamental engineering skill. The research questions were, (a) How proficient is the school’s mechanical engineering (ME) population in converting units of measurement? and (b) What are the differences between 1st year and senior students? The SoTL group consisted of seven ME faculty members at an engineering school in Puerto Rico and one invited researcher who performed the statistical analyses and assisted at all levels. The inquiry led to the creation of an objective test of unit conversions. The test was based on eight objectives identified by the researchers as essential in correctly converting units. Two questions were generated for each objective for a total of 16 questions. The ME faculty distributed the test in their courses and offered a 5% bonus incentive for answering the test (regardless of their score). The test results suggest that 1st year students are coming into the program with deficiencies in unit conversions; however, there is a statistically significant gain in half of the skills as the students progress through the curriculum. The worst performance in the test was converting metric prefixes, which is consistent with similar studies with U.S. students. Although an intervention to fix the problem is a future goal of the researchers, they recommend a major change in how unit conversions and metric prefixes are presented in textbooks and the NCEES FE Exam Reference Handbook.